Occupational Disease Prevention Strategies through OHS Interventions: Global Evaluation and Challenges - Ashari, Muhammad Rizki (Journal of Health Literacy and Qualitative Research, 2022)
Work-related diseases remain a significant global concern, necessitating robust Occupational Health and Safety (OHS) management systems to mitigate risks and ensure worker well-being. This study systematically reviews existing literature on OHS implementation and its effectiveness in preventing occupational illnesses. A comprehensive search of academic databases, including PubMed, Scopus, and Google Scholar, was conducted to analyze peer-reviewed studies published between 2015 and 2024. The selection criteria focused on empirical research evaluating the impact of OHS policies, worker training programs, and ergonomic interventions on workplace safety. The findings indicate that structured OHS strategies, such as continuous safety education, workplace ergonomic adjustments, and mental health integration, significantly enhance compliance with safety regulations and reduce occupational health risks. However, key challenges remain, including inadequate worker awareness, insufficient regulatory enforcement, and barriers to adopting technological innovations. Addressing these challenges requires increased investment in training programs, stronger legal frameworks, and the development of workplace safety technologies. This review underscores the need for a holistic approach to OHS management, integrating both physical and psychological health measures. Future research should explore long-term effectiveness assessments of OHS policies, sector-specific risk mitigation strategies, and advancements in digital safety monitoring. Strengthening OHS frameworks globally will contribute to improved workplace conditions, reduced disease incidence, and enhanced worker productivity.